COMPARISON OF SIMULTANEOUS VERSUS DELAYED VENTRICULOPERITONEAL SHUNTING IN PATIENTS UNDERGOING MENINGOCOELE REPAIR IN TERMS OF INFECTION - Khattak, Haider Ali; Gul, Nasim; Khan, Shahbaz Ali; Muhammad, Gul; Aurangzeb, Ahsan; Khan, Ibrahim; Khan, Abdul Hameed (Journal of Ayub Medical College Abbottabad, 2018)
Background: Myelomeningocele is a congenital anomaly of Central Nervous System (CNS) leading to serious sequels related to various systems and organs of the affected patient. Hydrocephalus is a common condition associated with myelomeningocele. Hydrocephalus is seen in 11.8% of children with Myelomeningocele (MMC). This study was conducted to compare the simultaneous vs delayed ventriculoperitoneal shunting in children undergoing myelomeningocele in terms of infection. Methods: This Randomized Control Trial was conducted at department of Neurosurgery, Ayub Medical College, Abbottabad from 7th March to 7th June 2016. In this study a total of 98 patients with MMC and hydrocephalus were randomly divided into two equal groups. In group A simultaneous MMC repair and VP shunting was performed while in group B MMC repair was done in first and VP shunting was done two weeks postoperatively. Results: In this study mean age in Group A was 1 years with SD±2.77 while mean age in Group B was 1 years with SD±3.12. In Group A (12%) patients had infection and (88%) whereas in Group B (20%) patients had infection and (80%) patients didn’t had infection. Conclusion: Simultaneous VP shunting was more effective than delayed VP shunting in children undergoing myelomeningocele in terms of infection. Keywords: Myelomeningocoele; spina bifida; delayed ventriculoperitoneal shunting; infection; complication